Rehabilitation therapy for children with autism based on interactive VR-motion serious game intervention: a randomized-controlled trial - Ma, Xufeng; Song, Kai (Frontiers in Public Health, 2025)
BackgroundAutism Spectrum Disorder (ASD) poses complex challenges in social communication, behavior, and learning, which traditional therapies often fail to fully address. This study explores an interactive VR-Motion serious game designed for children with ASD, leveraging immersive, controlled environments to enhance social skills, self-care, and emotional regulation.ObjectiveChildren with autism often suffer from multiple complications; thus, new serious games that are versatile and easy to use are more suitable for them. This study aims to design and develop a versatile serious game for multifaceted intervention in children with autism, encompassing psychological, social, and learning aspects. We also aim to evaluate the rationality of its design and the effectiveness of its content, with the ultimate goal of providing an effective intervention therapy for children with autism.Subjects and methodsThis study used the methods of pre-experiment and formal experiment. The pre-experiment (n = 2): Control group (Average Age = 123.8 months, SD = 32.27 months) experimental group (Average Age = 119.4 months, SD = 29.41 months), in which one male and one female was trained 4 times a week for 4 h each time for 3 weeks. The formal experiment (n = 19): random number sampling method was adopted to sample them into two groups for simultaneous intervention training, 4 times a week for 4 h each time for 16 weeks. (Average Age: 98.76–150.23 month, SD: 17.79–44.81 month, GSexratio: 5:4).ResultsThe analysis of formal experimental data shows that the design of this interactive VR-Motion serious game is reasonable and it has a good effect on the training of social communication and self-living ability of autistic children. In the post-test of wish tracking, df = 9; t = −1.155 and p = 0.281, it can be seen that the interactive VR-Motion serious game intervention has a good improvement on the social willingness of autistic children.ConclusionThe experimental results show that the design of interactive VR-Motion serious game provides excellent guidance for the simulation of autistic children’s attempts to socialize and experience warm social emotions and introduces correct life situations by cultivating their independent willingness to join social interactions during the game, and it has good benefits in establishing a stable learning environment.